The Training Market 2025 : Analyses based on the BIBB survey of newly concluded training contracts and the training market statistics of the Federal Employment Agency as of 30 September - Christ, Alexander [Verfasser]; Neuber-Pohl, Caroline [Verfasser]; Weller, Sabrina Inez [Verfasser]; Milde, Bettina [Verfasser]; Granath, Ralf-Olaf [Verfasser] (Bundesinstitut für Berufsbildung, 2026)
"In 2025, the situation on the training market worsened: despite rising demand, the number of training places and new training contracts fell again. The tense economic situation in Germany is thus also reflected in the training market. Around 84,400 young people were unsuccessful in their search for a training place. These are the key findings of the BIBB analysis on the development of the training market in 2025. The analysis is based on the BIBB survey of newly concluded training contracts and on the training market statistics of the Federal Employment Agency (BA), both as of 30 September. The publication provides a comprehensive overview of the training market in 2025 and current developments in supply and demand." (BIBB-Autorenreferat)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; 370; Ausbildungsstellenmarkt; Ausbildungsstellenbilanz; Ausbildungsplatzangebot; Ausbildungsplatznachfrage; Angebot-Nachfrage-Relation; Unbesetzte Ausbildungsplätze; Mismatch; Ausbildungsbeteiligung; Quantitative Angaben